Effects of oxidation on the localized surface plasmon resonance of Cu nanoparticles fabricated via vacuum coating. (February 2021) - Fang, Yingcui; Cheng, Zhitao; Wang, Shuai; Hao, Hongliang; Li, Lei; Zhao, Shiqi; Chu, Xiangqian; Zhu, Rensheng
Abstract: Cu is a kind of inexpensive plasmonic material but the applications based on the localized surface plasmon resonance (LSPR) of Cu nanoparticles (CuNPs) are limited. This is because CuNPs normally synthesized by chemical methods are prone to oxidization, and the absorption of Cu2 O, CuO, the interband transition of electrons from 3d to 4s overlap the LSPR of CuNPs, making the LSPR of CuNPs difficult to be identified. Herein, ultra-thin Cu films composed of CuNPs were fabricated by vacuum coating where oxidization of Cu was expected weak. However, no strong LSPR in the UV–Visible absorption spectra can be seen. In order to understand the mechanism, the as-deposited ultra-thin Cu films were annealed in nitrogen, oxygen and 5% hydrogen diluted nitrogen to mimic oxygen insufficient and sufficient oxidation, and reduction ambient to obtain Cu2 O, CuO and CuNPs respectively. By UV–Visible absorption spectroscopy, Field emission scanning electron microscopy, X-ray photoelectron spectroscopy, and surface enhanced Raman spectroscopy, the LSPR of CuNPs, the absorption of Cu2 O, CuO/Cu(OH)2 and interband transition were identified. The absorption spectra of the as-deposited ultra-thin Cu films, and their evolutions with the annealing temperature and time were explained. Finally, the oxygen sources are analyzed. Highlights: The ultra-thin Cu films composed of Cu nanoparticles (CuNPs) fabricated by vacuum coating don't show obvious LSPR. Strong LSPR of CuNPs can be obtained by annealing the ultra-thin Cu films in 5% hydrogen diluted nitrogen ambient. The absorption spectra of Cu2 O and CuO can be determined by annealing the ultra-thin Cu films in nitrogen and oxygen ambient. The LSPR of CuNPs with energy lower than interband transition still shows surface enhanced Raman scattering. The origins of oxidation of CuNPs were analyzed.